Implementing an adaptive reuse on industrial buildings: a proposal for transforming Erbil’s Silo in Kurdistan-Iraq into a hotel - Alfaris, Seema Khalid; Rafeeq, Dalia Ali; Sami, Sanar Sardar; Ahmed, Raghad Dlzar (Frontiers in Built Environment, 2024)
Industrial buildings, serving as markers of cultural heritage, connect our cultural identity from the past through the present and into the future. Unfortunately, many of these buildings lose their identity when they are converted into another function. Through the case study analysis (the Silo of Erbil City), a qualitative method is employed to examine design strategies and spatial transformations in recent adaptive reuse projects of existing structures. Through the literature review, this research investigates the importance of adaptive reuse and heritage buildings, underscoring their historical and theoretical underpinnings, and subsequently examines contemporary approaches to architectural criteria towards habitation for existing structures in the public, creative, and cultural domains. The study findings identify common fundamental elements of industrial heritage adaptive reuse and innovative design strategies applied in recent adaptive reuse projects, highlighting the potential to transform neglected or vacant abandoned buildings into urban open spaces. The study uses a comprehensive methodology involving case study analyses and diverse data collection techniques. The case study properties are the structural systems, natural lighting, and the surrounding open spaces. As a result, a hotel with a multipurpose hall, and a museum dedicated to the history of the Silo have been proposed, aiming at conserving the valuable heritage in this industrial area as well as providing an alternative perspective for the adaptive reuse of industrial structures in Erbil city. Finally, the implications of the research for the economic and social dimensions of urban development lie in understanding and promoting sustainable preservation strategies. This work is considered the first step for future research in Iraq, specifically in Kurdistan Region. The research concludes that the Silo of Erbil is one of the successful examples of the process of reusing buildings. It also concludes that less intervention in reusing a building can protect the building identity.